2-Deoxy-D-Glucose and ES-936 sensitize cancer- but not normal cells to both low- and high LET irradiation - Kratz, Katja; Förster, Henrieke; Vogel, Kira; Durante, Marco; Jakob, Burkhard (Frontiers in Oncology, 2025)
IntroductionMetabolic differences of normal- and cancer cells represent an important target for the development of novel cancer treatment strategies. Given that radiotherapy constitutes one of the primary treatment modalities for solid cancers, the targeting of cancer cell metabolism to enhance their sensitivity to irradiation emerges as a promising approach. The utilization of glycolysis even under aerobic conditions in cancer cells presents a unique target to deprive cancer cells of energy and metabolites required not only for their rapid cell growth but also for the repair of irradiation induced DNA damage. Furthermore, cancer cells have been observed to exhibit elevated levels of reactive oxygen species and potentially react more sensitively to an induced disturbance of the redox balance, especially after irradiation mediated oxidative stress. Overall, interference with aerobic glycolysis and the oxidative stress response could potentiate the anti-proliferative and cytotoxic effects of cancer cell irradiation, while sparing normal cells.MethodsTo analyze the effect of inhibitors targeting the cellular metabolism and redox balance, normal fibroblast- and cancer cell lines were characterized using a Seahorse XFp metabolic analyzer, followed by Sulforhodamin B proliferation assays and flow cytometry based cell cycle analysis. Furthermore, NADP+/NADPH-, NAD(P)H- and ROS levels were determined using bioluminescent assays, Fluorescence Lifetime Imaging Microscopy (FLIM) and fluorescent microscopy. Radiosensitization of cell lines was assessed through clonogenic survival assays and analyses of DNA-repair efficiency via fluorescence microscopy.ResultsThe present study demonstrates that the glycolytic inhibitor 2-deoxy-D-glucose and the NAD(P)H:quinone oxidoreductase inhibitor ES-936 can render cancer cells more sensitive to X-rays and densely ionizing radiation (high-linear energy transfer (LET) irradiation) like alpha-particles or heavy ions but do not affect normal fibroblasts. While inhibitor-treated and low-LET (X-ray) irradiated cancer cells exhibited a decreased clonal survival, an additional DNA repair defect was observed after high-LET irradiation.DiscussionOur results imply that distinct mechanisms influence the clonal survival and DNA repair of irradiated, inhibitor-treated cancer cells in dependence of the LET. The findings of this study suggest that the combination of inhibitors targeting glycolysis and the redox balance may represent a promising strategy to enhance the sensitivity of cancer cells to both photon- and charged particle therapy.